Effect of Firms Attributes on Financial Performance of Listed Industrial Goods Firms in Nigeria - Eneh, Catherine Amoge; Agu, Charles Ikechukwu; Nwankwo, Bobby Godwin Ogbogu; Agbachi, Vincent Onyeneke (ESUT JOURNAL OF SOCIAL SCIENCES, 2024)
The main objective of the study is to examine the extent to which firm attribute affects financial performance of listed industrial goods firm in Nigeria. The study specifically determined the extent to which firm size, firm liquidity, firm leverage affect net profit margin of industrial goods firm in Nigeria. The study adopted the ex-post facto research design. Secondary data was sourced from the annual reports of the sampled of five industrial goods firms for a ten (10) year period, spanning 2014 to 2023. The data collected were analyzed using descriptive analysis and multiple regression analysis. The findings of the study include: Firm Size have a positive and significant effect on the net profit margin of listed industrial goods firms in Nigeria (β = 2.1528; p-value = 0.0366); Firm liquidity have a negative non-significant effect on the net profit margin of listed industrial goods firms in Nigeria (β = 1.0242; p-value = 0.3111); Firm Leverage have a negative non-significant effect on the net profit margin of listed industrial goods firms in Nigeria (β = -1.1066; p-value = 0.2742). In conclusion, the goal of developing firm attribute is to create a strong and distinctive identity for a company which can lead to differentiation, brand recognition, customer loyalty and partnership and collaboration opportunities. The study recommended that listed industrial goods firms in Nigeria should strive for an optimal balance between liquidity and leverage financing by assessing their capital structure decisions to avoid excessive reliance on the leverage while also avoiding an overly cautious approach with too much liquidity financing.